The relationship between the concept 'art' and its institutionalisation during the period 1850-1871 in South Africa - Steyn, Pieter Andrew (Rhodes University, Faculty of Humanities, Department of Fine Art, 1985)
This research evolved as part of a personal struggle to understand my role as 'art' student. As such the essay is concerned with both the theory and practice of 'art', and the relationship between the two. It is, however, my experience of the lack of an analysis of the concept 'art' as a social and historical phenomenon, and the suppression of the politics of culture in most fine art courses, that has led me to concentrate on theoretical and political issues, rather than the formal aspects of painting. This essay is therefore not concerned with individual 'works of art', but with the general category 'art' as an organisational form. Despite its limitations, the essay goes beyond the personal by exploring some of the social, political, economic and cultural processes that form the broader social context in which the examination of 'art' should take place.
Keywords: Art, -- South African -- 19th century; Art -- Political aspects; Art and society -- South Africa